ISOLATION AND PHARMACOLOGICAL SCREENING OF 8-O-ACETYL HARPAGIDE FROM AJUGA BRACTEOSA WALL (Biological Sciences - PJSIR, 2004)
8-O-Acetyl harpagide was isolated and characterized from Ajuga bracteosa Wall, a species indigenous to Pakistan. Pharmacological screening of the compound for antibacterial, antifungal, antispasmodic, cardiotonic and antipyretic activities was carried out. The compound was found effective against a number of human pathogenic bacteria and fungi. Antispasmodic and cardiotonic effects elicited by the compound were also found. The compound also exhibited antipyretic activity when administered in the higher doses.